Firm performance improvement through ethical leadership and digital technology: The role of good corporate governance - Nur Chofifah; Syafnita Syafnita (Universitas Pekalongan, 2026)
This study analyzes how ethical leadership and digital technology contribute to firm performance improvement, with good corporate governance (GCG) playing a reinforcing role. In an increasingly competitive business environment and rapid digital transformation era, organizations—particularly micro, small, and medium enterprises (MSMEs)—are required to enhance leadership quality, leverage digital technologies, and apply sound governance principles to achieve sustainable performance. Ethical leadership is expected to foster trust, transparency, and responsible decision-making, while digital technology adoption enables firms to improve efficiency, productivity, and market access. Good corporate governance is assumed to support these relationships by strengthening accountability and organizational control. This research employs a quantitative approach using primary data collected through structured questionnaires distributed to MSME owners and managers. The collected data were analyzed using descriptive statistical analysis and moderated regression analysis (MRA) with the assistance of IBM SPSS. Ethical leadership, digital technology, good corporate governance, and firm performance were measured using Likert-scale instruments adapted from previous studies. The results indicate that ethical leadership has a positive and significant effect on firm performance. Digital technology adoption also positively influences firm performance. However, good corporate governance does not significantly moderate the relationship between ethical leadership and firm performance, nor the relationship between digital technology and firm performance. These findings suggest that while ethical leadership and digital technology directly enhance firm performance, governance practices in MSMEs remain insufficiently formalized to strengthen these effects. This study contributes to the literature by highlighting the combined role of leadership and digitalization in improving firm performance and provides practical implications for strengthening governance practices in MSMEs.